Manajemen dan Kepemimpinan: Dinamika di Pesantren Al-Muttaqien Pancasila Sakti - Syukron Muhammad; Wiji Hidayati (Lembaga Sosial Rumah Indonesia, 2023)
This research examines the management system and dynamics of Al-Muttaqien Pancasila Sakti Islamic boarding school in Karanganom, Klaten, Central Java. This boarding school has played a significant role in the education and development of Indonesian society since the era of the struggle for independence. The background of this research is that traditional Islamic boarding schools have undergone various changes in adapting to the modern era. The objective of this research is to understand how this boarding school manages its operations and identify the dynamics it experiences. This research employs a qualitative approach, collecting data through observations, interviews, and documentation. The results of the research indicate that the management of the boarding school involves structured processes of planning, organization, execution, and supervision. The boarding school has also undergone dynamics in the development of infrastructure, the establishment of formal educational institutions such as MTs and MA, and improvements in teaching methods. This research demonstrates that Al-Muttaqien Pancasila Sakti Islamic boarding school remains relevant in educating Indonesian society. The changes and adaptations made by this boarding school reflect its contribution to education and the development of human resources that align with the demands of the times.